Development and characterization of a microneedle-based sensor - Chan, Kenzo Zheng Long (Nanyang Technological University, 2024)
The proposed sensor is targeted to offer the potential for continuous and accurate monitoring of biomarkers, including glucose, oxygen, and drug compounds like codeine. The focus of this research would be on enhancing the sensor's performance through the deposition of gold nanoparticles and graphene oxide onto commercial electrodes, optimizing conditions for effective interaction with target analytes. By analyzing Cyclical Voltammograms, optimal concentrations of gold nanoparticles and graphene oxide are determined, facilitating sensor modification for improved functionality. Subsequently, the sensor's capabilities are evaluated through the detection of various target analyte concentrations. With the improved functionality, this study represents a significant step forward in wearable sensor technology for personalized healthcare monitoring, with potential applications spanning medical diagnostics, drug monitoring, and public health surveillance.